Chapter 10 - Sustainable engineering of food waste into high-quality animal feed using a drying technology - Santhana, Krishnan; Nur, Shahidah; Mohd Fadhil, Md Din; Puranjan, Mishra; Mohd Nasrullah, Zulkifli; Kadier, Abudukeremu; Shazwin, Mat Taib; Mohd Hafiz, Puteh; Norahim, Ibrahim; Nurfarhain, Md Rusli; Fadzlin, Md Sairan; Lakhveer, Singh (Elsevier, 2022)
Sustainable management through recycling of the food waste into animal feedstock is one of the promising approaches to overcome the food wastage-related issues. However, this action has been limited in some developed countries due to the lack of safety and security issues. Food waste contains high moisture content and it causes the spread-out of bacteria such as Escherichia coli, Salmonella, and sulfate reducing bacteria. The presence of these pathogens might cause food waste to be contaminated and causes infectious and pandemic diseases to human beings via animals. Thus this chapter aimed to discuss a case study where the evaluation of an effective method for food waste recycling is highlighted. As the food waste pre-drying facilities for the prerequisite animal feedstock pellets testimonial, this study ensures the end products processed inside the university (Universiti Teknologi Malaysia) are safe to be used as animal feeds by investigating the quality of end products. The observation reveals that solar drying food waste exhibits high protein and low moisture contents which the percentage is reached to 22% and 20%, respectively. Meanwhile, the oven drying method could reduce the E. coli content to only 500×103 CFU/g. Therefore, the solar drying method is the most effective to reduce high moisture content and able to achieve high protein content which is acceptable to be used as animal feeds.